Property owner shoreline modification decisions vary based on their perceptions of shoreline change and interests in ecological benefits - Amanda G. Guthrie; Sarah Stafford; Andrew M. Scheld; Karinna Nunez; Donna Marie Bilkovic (Frontiers in Marine Science, 2023)
Even under current sea level conditions, many communities are working to protect their coastlines against flooding and shoreline erosion. Coastal communities often protect their shorelines against excessive erosion by using armoring techniques (e.g., bulkheads, riprap). Yet hardened structures reduce many of the natural adaptive mechanisms present in coastal ecosystems and reduce the sustainability of the coastal system. In contrast, natural and nature-based features (e.g., living shorelines) can better protect coastal properties from storm damage and reduce erosion while also having the potential to adapt to new conditions. Since property owners are installing armoring structures more often than living shorelines, we sought to understand the factors motivating their shoreline modification decision. We surveyed property owners in Virginia, U.S. that applied for a shoreline modification permit. Most property owners, regardless of modification sought, perceive riprap revetment to be effective, able to withstand storm damage, and able to adapt to sea level rise. Interestingly, property owners that sought out living shorelines were not highly confident in living shorelines’ protection benefits. While most property owners perceived the ecological benefits of living shorelines, these benefits did not substantially impact the decision over what type of shoreline modification to implement. Our work highlights pathways that can improve coastal resilience given the important role that shoreline property owner decisions contribute to coastal community resiliency. Our results indicate there is a need to better engage property owners about the protection and adaptation benefits of living shorelines as their perceptions were not aligned with scientific assessments of living shorelines. Concurrently, coastal policies could be strengthened to support more natural approaches to shoreline management, as the more common armoring techniques are not resilient to sea level rise or storm damage.